Occupy Until I Come : A.T. Pierson And The Evangelization Of The World - Robert, Dana Lee. (Grand Rapids, Mich. : W.B. Eerdmans Pub., 2003)
Includes bibliographical references (p. 303-312) and index.
Keywords: Pierson, Arthur T. (Arthur Tappan), 1837-1911.; Presbyterian Church -- United States -- Clergy -- Biography; Evangelistic work -- United States -- History; Missions, American -- History; Protestantism -- 19th century; Pierson, Arthur -- Evangelism